Biochemical responses of Channa punctatus (Bl.) to industrial effluent induced stress during different phases of the reproductive cycle - Kaur, A; Kaur, K (Indian Journal of Fisheries, 2011)
The Effects of sublethal concentrations (3% and 15% v/v) of untreated nickelchrome electroplating effluent on the reproduction of female Channa punctatus were studied during preparatory, prespawning and spawning phases of the reproductive cycle. Both GSI and HSI of the exposed fish were lower as compared to control fish in all the phases. An irregular pattern of deposition of macromolecules (DNA, RNA and proteins) in liver as well as in ovaries indicated that exposed fish were not cycling properly due to stress. Alterations in the contents of macromolecules were greater in treatment T2 (15% v/v) than T1 (3% v/v) during all the phases.